2021
DOI: 10.1021/jacs.1c02664
|View full text |Cite
|
Sign up to set email alerts
|

REVEALR: A Multicomponent XNAzyme-Based Nucleic Acid Detection System for SARS-CoV-2

Abstract: Isothermal amplification strategies capable of rapid, inexpensive, and accurate nucleic acid detection provide new options for large-scale pathogen detection, disease diagnosis, and genotyping. Here we report a highly sensitive multicomponent XNA-based nucleic acid detection platform that combines analyte preamplification with X10−23-mediated catalysis to detect the viral pathogen responsible for COVID-19. The platform, termed RNA-Encoded Viral Nucleic Acid Analyte Reporter (REVEALR), functions with a detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 17 publications
(32 reference statements)
0
74
0
Order By: Relevance
“…To facilitate this study, an artificial plasmid model was constructed to validate the methodology. Genes fragments (wild-SARS-CoV-2, mut-SARS-CoV-2, FluA, MERS, rhinovirus, and SARS-CoV-1) were cloned into TOPO vectors with a T7 primer, using a TOPO PCR cloning kit (Beijing, China) ( Table S1 ) [ 25 ]. The vectors were obtained via a TIANpure Midi Plasmid Kit (Tiangen Biotech Co, Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate this study, an artificial plasmid model was constructed to validate the methodology. Genes fragments (wild-SARS-CoV-2, mut-SARS-CoV-2, FluA, MERS, rhinovirus, and SARS-CoV-1) were cloned into TOPO vectors with a T7 primer, using a TOPO PCR cloning kit (Beijing, China) ( Table S1 ) [ 25 ]. The vectors were obtained via a TIANpure Midi Plasmid Kit (Tiangen Biotech Co, Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…The developed X10-23 efficiently and persistently silenced gene activity via degradation of mRNA molecules in cultured mammalian cells. They also demonstrated the use of X10-23 to knock down allele-specific mRNA sequences in disease cells and to detect the viral pathogen responsible for COVID-19 with a detection limit of ≤20 aM [ 188 , 189 ]. To attain clear comprehension, a summary of the discussed nucleic-acid-based biosensors in this review is shown in Table 2 .…”
Section: Chemically Modified Nucleic Acid Analoguesmentioning
confidence: 99%
“…Among these, the commonly available are RNA-cleaved DNAzymes and G-quadruplex DNAzymes. Existing DNAzymes were used in current strategies for the detection and diagnosis of COVID-19 on a DNAzymes basis ( Tian et al, 2021 ; Yang and Chaput, 2021 ; Ahmad et al, 2021 ; Zhang et al, 2021a ). Although the selection of both aptamers and DNAzymes was done from ssDNA libraries, of which ssDNA libraries randomized and loaded up with RNA sequences serve for the selection of aptamers and DNAzymes, respectively.…”
Section: In Vitro Selection Of Functional Nucleic Acids Towards Understanding Covid-19mentioning
confidence: 99%
“… Detection Strategy Target Genes LOD Time Ref. Fluorescence Lateral flow readout S gene 20 aM 60 min Yang and Chaput (2021) RT-PCR Colorimetric readout N gene 1000 Copies of RNA ∼75 min Anantharaj et al (2020) RT-PCR Colorimetric readout N gene 100 Copies of RNA <1 h Ahmad et al (2021) Chemiluminescence Immunoassay SARS-CoV-2 antibodies 6.46 fg mL −1 ∼140 min ( Zhang et al, 2021a ) Logic DNA circuit Fluorescent nucleotide 3562–3581 and 32442–32461 of the COVID-19 complete genome 3.3 fM 75 min Pan et al (2021) Electrochemical N protein 8.33 pg mL −1 Unknown Tian et al (2021) …”
Section: Functional Nucleic Acid-based Diagnostic Strategies For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation